Cav2.3 channel function and Zn2+-induced modulation: potential mechanisms and (patho)physiological relevance. Issue 1 (1st January 2020) - Neumaier, Felix; Schneider, Toni; Albanna, Walid
ABSTRACT: Voltage-gated calcium channels (VGCCs) are critical for Ca 2+ influx into all types of excitable cells, but their exact function is still poorly understood. Recent reconstruction of homology models for all human VGCCs at atomic resolution provides the opportunity for a structure-based discussion of VGCC function and novel insights into the mechanisms underlying Ca 2+ selective flux through these channels. In the present review, we use these data as a basis to examine the structure, function, and Zn 2+ -induced modulation of Cav 2.3 VGCCs, which mediate native R-type currents and belong to the most enigmatic members of the family. Their unique sensitivity to Zn 2+ and the existence of multiple mechanisms of Zn 2+ action strongly argue for a role of these channels in the modulatory action of endogenous loosely bound Zn 2+, pools of which have been detected in a number of neuronal, endocrine, and reproductive tissues. Following a description of the different mechanisms by which Zn 2+ has been shown or is thought to alter the function of these channels, we discuss their potential (patho)physiological relevance, taking into account what is known about the magnitude and function of extracellular Zn 2+ signals in different tissues. While still far from complete, the picture that emerges is one where Cav 2.3 channel expression parallels the occurrence of loosely bound Zn 2+ pools in different tissues and where these channels may serve to translate physiological Zn 2+ signals into changes of electrical activity and/or intracellular Ca 2+ levels.